Natural foods resources and dietary ingredients for the amelioration of Helicobacter pylori infection - Wang, Chengyuan; Yao, Meixiang; Zhong, Hongguang; Meena, Stephene S.; Shu, Fuxing; Nie, Shaoping; Xie, Mingyong (Frontiers in Medicine, 2023)
Helicobacter pylori (H. pylori) is a gastric-persistent pathogen that can cause peptic ulcer disease, gastric cancer, and mucosal-associated lymphoid tissue lymphoma. This pathogen is commonly treated with antibiotic-based triple or quadruple therapy. However, antibiotic therapy could result in the bacterial resistance, imbalance of gut microbiota, and damage to the liver and kidneys, etc. Therefore, there is an urgent need for alternative therapeutic strategies. Interestingly, natural food resources, like vegetables, fruits, spices, and edible herbs, have potent inhibitory effects on H. pylori. In this review, we systematically summarized these foods with supporting evidence from both animal and clinical studies. The results have indicated that natural foods may possess temporary inhibition effect on H. pylori rather than durable eradication, and may help to reduce H. pylori colonization, enhance the effect of antibiotics and modulate the host’s immune response.